Neodymium-iron-boron magnetic material with composite anti-corrosion coating and preparation method and application of neodymium-iron-boron magnetic material
Through the comprehensive methods of sandblasting, arc spraying, magnetron sputtering and plasma nitriding treatment, the corrosion problem of neodymium iron boron magnets in humid and hot environments is solved, and its anti-corrosion and wear resistance are significantly improved.
Patent Information
- Application Number
- CN202411733512.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
Existing neodymium iron boron magnets are prone to oxidative corrosion and electrochemical corrosion in humid and hot environments, resulting in insufficient corrosion resistance.
After sandblasting treatment, an aluminum alloy coating is sprayed on the surface of the neodymium iron boron matrix, and the aluminum film layer is sputtered by magnetron sputtering method, and finally plasma nitriding or passivation treatment is performed to improve the hardness and wear resistance of the coating.
It significantly improves the corrosion resistance and wear resistance of neodymium iron boron magnetic materials, has strong bonding power between the coating and the substrate, and can resist salt spray for more than 500 hours.
Smart Images

Figure BDA0005161032340000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of NdFeB, and in particular to a NdFeB magnetic material with a composite anti-corrosion coating, and a preparation method and application thereof. Background Art
[0002] NdFeB magnets are widely used in medical, transportation, aerospace and other fields due to their excellent comprehensive magnetic properties. In recent years, NdFeB magnets have also begun to be widely used in household appliances, new energy vehicles and wind power generation.
[0003] However, NdFeB magnets have poor chemical stability and are prone to oxidation under daily use conditions. They are prone to severe electrochemical corrosion when exposed to hot and humid conditions.
[0004] In order to prevent NdFeB magnets from oxidation corrosion and electrochemical corrosion and improve their corrosion resistance, the commonly used surface protection treatment methods can be divided into: electroplating, chemical plating, chemical conversion film, electrophoresis and vacuum plating, etc., to obtain metal or alloy film layers, polymer coatings, chemical conversion film layers and composite coatings. Among them, vacuum coating technology does not produce wastewater and waste gas that are harmful to the environment during the production process. Compared with other surface treatment methods, it is more environmentally friendly and widely used in NdFeB surface protection. Aluminum has excellent corrosion resistance because it can spontaneously form a dense oxide film layer in the air, but its low hardness and poor wear resistance limit its application in harsh environments. The prior art CN116356314A discloses that an aluminum alloy film layer is cold-sprayed on the surface of a neodymium iron boron magnet and then an ion nitriding treatment is performed to form a nitriding layer with a thickness of 5-15 μm to obtain a film layer with high corrosion resistance, high hardness and high wear resistance. However, due to the large thickness of the nitriding layer, the surface of the film layer is prone to cracking, and the bonding strength between the nitriding layer and the aluminum alloy film layer is affected, thereby reducing the reliability of the neodymium iron boron magnet during application.
[0005] Therefore, it is necessary to develop new technology to set an aluminum-containing film layer with high wear resistance on the surface of NdFeB. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a NdFeB magnetic material with a composite anti-corrosion coating, and a preparation method and use thereof. By sandblasting the surface of the NdFeB substrate and then spraying an aluminum alloy coating on the surface, sputtering an aluminum film layer, and performing plasma nitriding or passivation treatment, the hardness and wear resistance of the coating can be significantly improved. The obtained NdFeB magnetic material has excellent anti-corrosion performance and broad application prospects.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a NdFeB magnetic material having a composite anti-corrosion coating, the preparation method comprising the following steps:
[0009] The NdFeB substrate is sandblasted to obtain a sandblasted NdFeB substrate; an aluminum alloy coating is sprayed on the surface of the sandblasted NdFeB substrate by an arc spraying method to obtain a first substrate; an aluminum film layer is sputtered on the surface of the aluminum alloy coating of the first substrate by a magnetron sputtering method to obtain a second substrate; the second substrate is plasma nitrided or passivated to obtain a NdFeB magnetic material with a composite anti-corrosion coating.
[0010] Compared with the existing vacuum aluminum coating technology, the present invention combines arc spraying and magnetron sputtering, and finally adopts nitriding or passivation treatment to enhance the wear resistance of the coating, wherein an arc spraying method is used to form an aluminum alloy coating on the surface of the NdFeB substrate, which greatly improves production efficiency and ensures the bonding strength between the aluminum alloy film layer and the substrate; a magnetron sputtering method is used to sputter an aluminum film layer on the surface of the aluminum alloy coating to ensure the compactness of the aluminum film layer, and by setting the aluminum film layer as a transition film layer, on the one hand, the pore space on the surface of the aluminum alloy coating can be sealed by magnetron sputtering aluminum atoms, thereby improving the overall corrosion resistance of the anti-corrosion coating; on the other hand, it can provide a film-forming platform for subsequent plasma nitriding or passivation treatment to prevent active nitrogen atoms and passivation liquid from contacting the NdFeB substrate.
[0011] Preferably, the blasting material for the sandblasting comprises brown corundum and / or quartz sand.
[0012] Preferably, the blasting material particle size is 14-40 mesh, for example, it can be 14 mesh, 17 mesh, 20 mesh, 23 mesh, 26 mesh, 29 mesh, 32 mesh, 35 mesh, 38 mesh or 40 mesh.
[0013] Preferably, the sandblasting pressure is 0.1-0.5 MPa, for example, it may be 0.1 MPa, 0.15 MPa, 0.19 MPa, 0.24 MPa, 0.28 MPa, 0.33 MPa, 0.37 MPa, 0.42 MPa, 0.46 MPa or 0.5 MPa.
[0014] Preferably, the sandblasting time is 5 to 15 minutes, for example, it can be 5 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes.
[0015] Preferably, in the arc spraying method, the angle between the arc spray gun and the conductive nozzle is 30-60°, for example, 30°, 34°, 37°, 40°, 44°, 47°, 50°, 54°, 57° or 60°.
[0016] Preferably, the diameter of the aluminum alloy wire in the arc spraying method is 2 to 3 mm, for example, it can be 2 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm or 3 mm.
[0017] Preferably, in the arc spraying method, the distance from the arc spray gun to the workpiece surface is 150-200 mm, for example, it can be 150 mm, 156 mm, 162 mm, 167 mm, 173 mm, 178 mm, 184 mm, 189 mm, 195 mm or 200 mm.
[0018] Preferably, the operating voltage in the arc spraying method is 30-35V, for example, 30V, 31V, 32V, 33V, 34V or 35V.
[0019] Preferably, the operating current in the arc spraying method is 180-220A, for example, it can be 180A, 183A, 185A, 187A, 189A, 192A, 194A, 196A, 198A, 200A or 220A.
[0020] When the present invention is directed to a special NdFeB substrate, special limiting current parameters are required in the arc spraying process. The working current affects the temperature during the arc spraying process. A working current exceeding 220A leads to a higher temperature during the arc spraying process, thereby reducing the magnetic properties of the NdFeB magnet.
[0021] Preferably, the pressure of the compressed air in the arc spraying method is not less than 0.5 MPa, for example, it can be 0.5 MPa, 0.52 MPa, 0.53 MPa, 0.55 MPa, 0.58 MPa, 0.6 MPa, 0.65 MPa, 0.68 MPa or 0.7 MPa.
[0022] Preferably, the flow rate of compressed air in the arc spraying method is not less than 2.0 m 3 / min, for example, it can be 2.0m 3 / min, 2.1m 3 / min、2.5m 3 / min、2.8m 3 / min、3.0m 3 / min、3.2m 3 / min、3.5m 3 / min or 4.0m 3 / min, etc.
[0023] Preferably, the thickness of the aluminum alloy coating is 50-200 μm, for example, it can be 50 μm, 67 μm, 84 μm, 100 μm, 117 μm, 134 μm, 150 μm, 167 μm, 184 μm or 200 μm.
[0024] The present invention further preferably has a thickness of the aluminum alloy coating within the above range. When the thickness of the aluminum alloy coating is too thin, it is difficult to fully ensure the surface protection effect of the aluminum alloy film layer on the NdFeB substrate.
[0025] Preferably, the aluminum content in the aluminum alloy coating is 80-90at%, for example, it can be 80at%, 82at%, 83at%, 84at%, 85at%, 86at%, 87at%, 88at%, 89at% or 90at%.
[0026] Preferably, the material of the aluminum alloy coating includes any one of aluminum-nickel alloy, aluminum-titanium alloy, aluminum-chromium alloy or aluminum-magnesium alloy, or a combination of at least two thereof.
[0027] Preferably, between the sprayed aluminum alloy coating and the sputtered aluminum film layer, the preparation method further comprises: sequentially performing baking degassing and ion bombardment cleaning on the first substrate.
[0028] Preferably, the baking and degassing temperature is 180-270°C, for example, it can be 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C.
[0029] Preferably, the baking and degassing time is 30 to 60 min, for example, it can be 30 min, 34 min, 37 min, 40 min, 44 min, 47 min, 50 min, 54 min, 57 min or 60 min.
[0030] Preferably, the ion bombardment cleaning is performed using an inert gas.
[0031] Preferably, the inert gas is argon.
[0032] Preferably, the negative bias voltage in the ion bombardment cleaning is 800-1500V, for example, 800V, 870V, 950V, 1030V, 1110V, 1180V, 1260V, 1345V, 1420V or 1500V.
[0033] Preferably, the ion bombardment cleaning time is 5 to 15 minutes, for example, it can be 5 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes.
[0034] Preferably, the purity of the aluminum target material used is not less than 99.9 wt %.
[0035] Preferably, the vacuum degree in the magnetron sputtering method is 6.5×10 -3 ~3.0×10 -3 Pa, for example, can be 6.5×10 -3 Pa, 6.0×10 -3 Pa, 5.5×10 -3 Pa, 5.0×10 -3 Pa, 4.5×10 -3 Pa, 4.0×10 -3 Pa, 3.5×10 -3 Pa or 3.0×10 -3 Pa et al.
[0036] Preferably, the working gas in the magnetron sputtering method is argon.
[0037] Preferably, the working gas pressure in the magnetron sputtering method is 0.1-1 Pa, for example, it can be 0.1 Pa, 0.2 Pa, 0.3 Pa, 0.4 Pa, 0.5 Pa, 0.6 Pa, 0.7 Pa, 0.8 Pa, 0.9 Pa or 1 Pa.
[0038] Preferably, when the magnetron sputtering method adopts a through-type magnetron sputtering coating production line, the sputtering current is 50-80A, for example, it can be 50A, 54A, 57A, 60A, 64A, 67A, 70A, 74A, 77A or 80A, and the sputtering time is 10-20min, for example, it can be 10min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min or 20min, etc. Alternatively, when the magnetron sputtering method adopts a single-body coating machine, the coating current is 10 to 30 A, for example, it can be 10A, 13A, 15A, 17A, 19A, 22A, 24A, 26A, 28A or 30A, and the coating time is 20 to 60 min, for example, it can be 20 min, 25 min, 29 min, 34 min, 38 min, 43 min, 47 min, 52 min, 56 min or 60 min, etc.
[0039] Preferably, the thickness of the aluminum film layer is 1-2 μm, for example, 1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm.
[0040] Preferably, the vacuum degree of the plasma nitriding treatment is 1-10 Pa, for example, it can be 1 Pa, 2 Pa, 3 Pa, 4 Pa, 5 Pa, 6 Pa, 7 Pa, 8 Pa, 9 Pa or 10 Pa.
[0041] Preferably, the nitriding temperature of the plasma nitriding treatment is 200-300°C, for example, it can be 200°C, 212°C, 223°C, 234°C, 245°C, 256°C, 267°C, 278°C, 289°C or 300°C.
[0042] Preferably, the nitriding time of the plasma nitriding treatment is 20 to 60 min, for example, it can be 20 min, 25 min, 30 min, 33 min, 38 min, 40 min, 45 min, 50 min, 55 min or 60 min.
[0043] It is worth noting that the nitriding time directly affects the diffusion depth of nitrogen atoms (the thickness of the aluminum nitride film). If the nitriding time is long, the aluminum nitride film formed is thicker. Since aluminum nitride is a non-metallic material, the internal stress between the film layers increases, which can easily cause cracks on the coating surface. If the nitriding time is lower than the nitriding time, the hardness of the film layer cannot be effectively improved, and the improvement of the wear resistance of the film layer is limited.
[0044] Preferably, the gas used in the plasma nitriding treatment is NH3 with a purity of not less than 99%.
[0045] Preferably, the nitriding gas pressure of the plasma nitriding treatment is 100-600 Pa, for example, it can be 100 Pa, 156 Pa, 212 Pa, 267 Pa, 323 Pa, 378 Pa, 434 Pa, 489 Pa, 545 Pa or 600 Pa.
[0046] Preferably, the current density of the plasma nitriding treatment is 0.5-5 mA / cm 2 , for example, it can be 0.5 mA / cm 2 , 1mA / cm 2 , 1.5mA / cm 2 , 2mA / cm 2 , 2.5mA / cm 2 , 3mA / cm 2 , 3.5mA / cm 2 , 4mA / cm 2 , 4.5mA / cm 2 or 5mA / cm 2 wait.
[0047] Preferably, the voltage of the plasma nitriding treatment is 600-800V, for example, 600V, 620V, 645V, 660V, 685V, 715V, 735V, 750V, 770V or 800V, etc. Preferably, the passivation solution of the passivation treatment comprises a passivating agent, and the passivating agent comprises any one or a combination of at least two of potassium molybdate, sodium molybdate or nitric acid, wherein a typical but non-limiting combination is a combination of potassium molybdate and sodium molybdate, a combination of nitric acid and sodium molybdate, and a combination of potassium molybdate and nitric acid.
[0048] Preferably, the passivation time of the passivation treatment is 4 to 15 min, for example, it can be 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min.
[0049] Preferably, the passivation temperature of the passivation treatment is 30-50°C, for example, it may be 30°C, 32°C, 33°C, 34°C, 35°C, 36°C, 38°C, 40°C, 42°C, 45°C, 48°C or 50°C.
[0050] Preferably, the composition of the NdFeB matrix includes 28.5-32wt% of R element, 0.86-1.02wt% of B element, 0-4wt% of M element excluding 0, and the balance T.
[0051] Wherein, R represents a rare earth element selected from Nd and at least one of the following rare earth elements: Pr, La, Ce, Dy, Tb and Ho.
[0052] M is selected from any one of Cu, Ga, Zr, Ti, Nb, Al, Ag, Co or W, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of Cu and Zr, a combination of Co and Ga, a combination of W and Ga, a combination of Cu and W, a combination of Zr and Ga, a combination of Ag and Zr, and a combination of Ti and Al.
[0053] T includes Fe and other impurity elements, wherein Fe accounts for more than 97wt% of the total amount of T, for example, it can be 97wt%, 97.3wt%, 97.5wt%, 97.7wt%, 97.9wt%, 98.2wt%, 98.4wt%, 98.6wt%, 98.8wt% or 99wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0054] Specifically, 28.5-32wt% of the R element may be, for example, 28.5wt%, 28.9wt%, 29.3wt%, 29.7wt%, 30.1wt%, 30.5wt%, 30.9wt%, 31.3wt%, 31.7wt% or 32wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable; 0.86-1.02wt% of the B element may be, for example, 0.86wt%, 0.88wt%, 0.9wt%, 0.92wt%, 0.94wt%, etc. t%, 0.95wt%, 0.97wt%, 0.99wt%, 1.01wt% or 1.02wt%, etc., but not limited to the listed values, and other values not listed within the range are equally applicable; 0-4wt% of the M element and not including 0, for example, 0.1wt%, 0.5wt%, 0.9wt%, 1.4wt%, 1.8wt%, 2.3wt%, 2.7wt%, 3.2wt%, 3.6wt% or 4wt%, etc., but not limited to the listed values, and other values not listed within the range are equally applicable.
[0055] As a preferred technical solution of the present invention, the method for preparing the NdFeB magnetic material comprises the following steps:
[0056] (1) using brown corundum and / or quartz sand with a particle size of 14 to 40 meshes to sandblast the NdFeB substrate, the sandblasting pressure is 0.1 to 0.5 MPa, the time is 5 to 15 minutes, and the NdFeB substrate after sandblasting is obtained;
[0057] (2) spraying an aluminum alloy coating on the surface of the sandblasted NdFeB substrate by an arc spraying method to obtain a first substrate; wherein the angle between the arc spray gun and the conductive nozzle is 30 to 60 degrees, the diameter of the aluminum alloy wire is 2 to 3 mm, the distance from the arc spray gun to the workpiece surface is 150 to 200 mm, the working voltage is 30 to 35 V, the working current is 180 to 220 A, the pressure of the compressed air is not less than 0.5 MPa, and the flow rate of the compressed air is not less than 2.0 m 3 / min;
[0058] (3) baking and degassing the first substrate at 180-270° C. for 30-60 min, and then ion bombarding cleaning with argon gas for 5-15 min, wherein the negative bias voltage during the ion bombardment cleaning is 800-1500 V, to obtain a cleaned first substrate;
[0059] (4) A magnetron sputtering method is used to sputter an aluminum film layer on the aluminum alloy coating surface of the cleaned first substrate, the purity of the aluminum target material used is not less than 99.9wt%, and the vacuum degree is 6.5×10 -3 Pa~3.0×10 -3Pa, the working gas is argon, and the working gas pressure is 0.1-1 Pa; when the magnetron sputtering method adopts a through-type magnetron sputtering coating production line, the sputtering current is 50-80A, and the sputtering time is 10-20min; or, when the magnetron sputtering method adopts a single-body coating machine, the coating current is 10-30A, and the coating time is 20-60min, to obtain a second substrate;
[0060] (5) The second substrate is subjected to plasma nitriding treatment, wherein the vacuum degree of the plasma nitriding treatment is 1-10 Pa, the nitriding temperature is 200-300° C., the nitriding time is 20-60 min, the gas used is NH3 with a purity of not less than 99%, the nitriding pressure is 100-600 Pa, and the current density is 0.5-5 mA / cm 2 , the voltage is 600-800V, and the NdFeB magnetic material with a composite anti-corrosion coating is obtained;
[0061] Alternatively, the second substrate is passivated at 30-50° C. for 4-15 minutes, and the passivation solution of the passivation treatment includes a passivator, and the passivator includes any one or a combination of at least two of potassium molybdate, sodium molybdate or nitric acid to obtain a NdFeB magnetic material with a composite anti-corrosion coating.
[0062] In a second aspect, the present invention provides a NdFeB magnetic material with a composite anti-corrosion coating, wherein the NdFeB magnetic material with a composite anti-corrosion coating is prepared by the method for preparing the NdFeB magnetic material with a composite anti-corrosion coating described in the first aspect.
[0063] In a third aspect, the present invention provides a NdFeB magnetic material with a composite anti-corrosion coating as described in the first aspect, and / or a NdFeB magnetic material prepared by the preparation method as described in the second aspect, and their use in automobiles, electrical appliances, new energy or medical equipment.
[0064] Compared with the prior art, the present invention has at least the following beneficial effects:
[0065] (1) The preparation method of the NdFeB magnetic material with a composite anti-corrosion coating provided by the present invention adopts arc spraying to prepare an aluminum alloy coating technology, which greatly improves the production efficiency and shortens the time required for preparing the aluminum alloy coating to 1% to 30% of the time required for film formation using traditional magnetron sputtering technology; and a magnetron sputtering method is used to sputter an aluminum film layer on the surface of the aluminum alloy coating to ensure the density of the aluminum film layer. The aluminum film layer serves as a transition film layer. On the one hand, it can seal the pore space on the surface of the aluminum alloy coating by magnetron sputtering aluminum atoms, thereby improving the overall corrosion resistance of the anti-corrosion coating; on the other hand, it can provide a film-forming platform for subsequent plasma nitriding or passivation treatment, thereby blocking the contact between active nitrogen atoms or passivation liquid and the NdFeB matrix, thereby improving the overall wear resistance of the composite anti-corrosion coating.
[0066] (2) The NdFeB magnetic material with a composite anti-corrosion coating provided by the present invention has excellent anti-corrosion performance, and its salt spray resistance test can reach more than 500 hours. In addition, the bonding strength between the coating and the NdFeB substrate is strong, reaching more than 26.5MPa. DETAILED DESCRIPTION
[0067] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0068] Example 1
[0069] The present embodiment provides a NdFeB magnetic material with a composite anti-corrosion coating, and the preparation method of the NdFeB magnetic material comprises the following steps:
[0070] (1) using brown corundum with a particle size of 30 mesh to sandblast a NdFeB matrix (composition includes 31.7wt% of Pr and Nd (the mass ratio of the two is 1:1), 0.86wt% of B, 1.5wt% of M (M includes 0.5wt% Ga, 0.2wt% Cu, 0.3wt% Al, 0.5wt% Co), and the balance T, T includes Fe and other impurity elements, wherein Fe accounts for 99.6wt% of the total amount of T) with a sandblasting pressure of 0.3MPa and a time of 10min to obtain a sandblasted NdFeB matrix;
[0071] (2) an aluminum alloy coating (with an aluminum content of 80 at % and a chromium content of 20 at %) is sprayed on the surface of the sandblasted NdFeB substrate by an arc spraying method to obtain a first substrate; wherein the arc spraying equipment includes an arc spray gun, a control box, a power supply and a wire feeding mechanism, the angle between the arc spray gun and the conductive nozzle is 40°, the diameter of the aluminum alloy wire is 2.5 mm, the distance from the arc spray gun to the workpiece surface is 180 mm, the working voltage is 32 V, the working current is 190 A, the pressure of the compressed air is 0.6 MPa, and the flow rate of the compressed air is 2.5 m 3 / min, spraying time 5min;
[0072] (3) baking the first substrate at 250° C. for degassing for 45 minutes, and then using argon gas for ion bombardment cleaning for 10 minutes, with a negative bias voltage of 1200 V during the ion bombardment cleaning, to obtain a cleaned first substrate;
[0073] (4) A magnetron sputtering method is used to sputter an aluminum film layer on the aluminum alloy coating surface of the cleaned first substrate, the purity of the aluminum target material used is not less than 99.9wt%, and the vacuum degree is 4.2×10 -3Pa, the working gas is argon, and the working gas pressure is 0.5Pa; the magnetron sputtering method adopts a through-type magnetron sputtering coating production line, the sputtering current is 70A, and the sputtering time is 15min to obtain a second substrate;
[0074] (5) The second substrate is subjected to plasma nitriding treatment. The ion nitriding equipment used includes a DC ion power supply, a vacuum furnace, a vacuum acquisition system, a measurement system and a gas supply system. The vacuum degree of the plasma nitriding treatment is 5 Pa, the nitriding temperature is 200° C., the nitriding time is 50 min, the gas used is NH3 with a purity of 99.9wt%, the nitriding gas pressure is 150 Pa, and the current density is 2.0 mA / cm 2 , the voltage is 700V, and the NdFeB magnetic material with a composite anti-corrosion coating is obtained.
[0075] Example 2
[0076] The present embodiment provides a NdFeB magnetic material with a composite anti-corrosion coating, and the preparation method of the NdFeB magnetic material comprises the following steps:
[0077] (1) using brown corundum with a particle size of 40 mesh to sandblast a NdFeB matrix (composition includes 29.8wt% of Pr and Nd (the mass ratio of the two is 0.8:1), 0.9wt% of B, 1.3wt% of (M elements include 0.4wt% Ga, 0.3wt% Cu, 0.3wt% Al, 0.3wt% Ti) elements, and the balance T, T includes Fe and other impurity elements, wherein Fe accounts for 99.5wt% of the total amount of T) with a sandblasting pressure of 0.1MPa and a time of 10min to obtain a sandblasted NdFeB matrix;
[0078] (2) an aluminum alloy coating (with an aluminum content of 85 at %, and a nickel content of 15 at %) is sprayed on the surface of the sandblasted NdFeB substrate by an arc spraying method to obtain a first substrate; wherein the arc spraying equipment includes an arc spray gun, a control box, a power supply and a wire feeding mechanism, the angle between the arc spray gun and the conductive nozzle is 45°, the diameter of the aluminum alloy wire is 3 mm, the distance from the arc spray gun to the workpiece surface is 200 mm, the working voltage is 35 V, the working current is 200 A, the pressure of the compressed air is 0.5 MPa, and the flow rate of the compressed air is 3.0 m 3 / min, spraying time 8min;
[0079] (3) baking the first substrate at 230° C. for degassing for 60 min, and then using argon gas for ion bombardment cleaning for 5 min, with a negative bias voltage of 1500 V during the ion bombardment cleaning, to obtain a cleaned first substrate;
[0080] (4) A magnetron sputtering method is used to sputter an aluminum film layer on the aluminum alloy coating surface of the cleaned first substrate, the purity of the aluminum target material used is not less than 99.9wt%, and the vacuum degree is 6.5×10 -3 Pa, the working gas is argon, and the working gas pressure is 0.1 Pa; the magnetron sputtering method adopts a through-type magnetron sputtering coating production line, the sputtering current is 60A, and the sputtering time is 10min to obtain a second substrate;
[0081] (5) The second substrate is subjected to plasma nitriding treatment. The ion nitriding equipment used includes a DC ion power supply, a vacuum furnace, a vacuum acquisition system, a measurement system and a gas supply system. The vacuum degree of the plasma nitriding treatment is 1 Pa, the nitriding temperature is 220° C., the nitriding time is 60 min, the gas used is NH3 with a purity of 99.5wt%, the nitriding gas pressure is 200Pa, and the current density is 5mA / cm 2 , the voltage is 600V, and the NdFeB magnetic material with a composite anti-corrosion coating is obtained.
[0082] Example 3
[0083] The present embodiment provides a NdFeB magnetic material with a composite anti-corrosion coating. The NdFeB magnetic material is the same as in Example 1 except that the second substrate is passivated in step (5). The passivation solution is 15 g / L sodium molybdate and 6 g / L sodium dodecylbenzene sulfonate. The passivation temperature is 40°C and the passivation time is 5 min. The rest is the same as in Example 1 and will not be repeated here.
[0084] Example 4
[0085] This embodiment provides a NdFeB magnetic material with a composite anti-corrosion coating. The NdFeB magnetic material is the same as that of Embodiment 1 except that step (3) is not performed, and will not be described in detail here.
[0086] Example 5
[0087] This embodiment provides a NdFeB magnetic material with a composite anti-corrosion coating. The NdFeB magnetic material is the same as that in Embodiment 1 except that the nitriding temperature of the plasma nitriding treatment is 350° C., and will not be described in detail here.
[0088] Example 6
[0089] This embodiment provides a NdFeB magnetic material with a composite anti-corrosion coating. The NdFeB magnetic material is the same as that in Embodiment 1 except that the working current of the arc spraying is 230A, and thus will not be described in detail.
[0090] Comparative Example 1
[0091] This comparative example provides a NdFeB magnetic material. The NdFeB magnetic material is the same as Example 1 except that the sandblasting in step (1) is not performed, and the details are not repeated here.
[0092] Comparative Example 2
[0093] This comparative example provides a NdFeB magnetic material. The NdFeB magnetic material is the same as Example 1 except that step (4) is not performed, and the details are not repeated here.
[0094] Comparative Example 3
[0095] This comparative example provides a NdFeB magnetic material. The NdFeB magnetic material is the same as Example 1 except that the arc spraying method is replaced by magnetron sputtering, and the rest is not repeated here.
[0096] Specifically, the aluminum alloy coating (with the same composition as in Example 1) was sputtered on the surface of the NdFeB substrate after sandblasting by magnetron sputtering, and the vacuum degree was 4.2×10 -3 Pa, the working gas is argon, and the working gas pressure is 0.5 Pa; the magnetron sputtering method adopts a through-type magnetron sputtering coating production line, the sputtering current is 70A, and the sputtering time is 300min.
[0097] Comparative Example 4
[0098] This comparative example provides a NdFeB magnetic material. The NdFeB magnetic material is the same as Example 1 except that step (5) is not performed, and the details are not repeated here.
[0099] Test methods and conditions:
[0100] 1) Salt spray test conditions are: temperature 35±2℃, 50±5g / LNaCl, splashing speed 1~2ml / 80cm2h, pH: 6.5~7.2.
[0101] 2) Coating thickness test: Measure the average value of multiple groups (such as three groups) of thickness at different sampling areas of the workpiece to be tested.
[0102] 3) High temperature demagnetization performance test of magnet: the test temperature is 150℃, high temperature demagnetization rate = [(normal temperature magnetic flux) - (magnet flux returning to normal temperature after a period of high temperature)) / (magnet flux at normal temperature) * 100%)].
[0103] 4) Bonding strength test: The bonding strength between the coating and the substrate is tested by a pull-out test.
[0104] 5) Wear resistance test: The friction and wear test was carried out by line contact reciprocating sliding mode, with a loading force of 1N, a relative movement speed of 3mm / s, a round trip stroke of 10mm, and 5000 wear times.
[0105] The test results of the above embodiments and comparative examples are shown in Table 1.
[0106] Table 1
[0107]
[0108] From Table 1, we can see the following points:
[0109] (1) It can be seen from Examples 1 to 3 that the preparation method of the NdFeB magnetic material with a composite anti-corrosion coating provided by the present invention combines arc spraying technology with magnetron sputtering technology, and assists with plasma nitriding or passivation treatment, which not only meets the requirement that the thickness of the anti-corrosion coating is within 100 microns, but also can obtain a salt spray resistance time of ≥572h, and a weight loss of ≤13% in the wear resistance test, a bonding force of up to 27.8MPa, and a high-temperature demagnetization rate of less than 0.8%, with excellent comprehensive performance and broad application prospects;
[0110] (2) It can be seen from the combination of Example 1 and Example 4 that Example 1 first performs ion bombardment cleaning in step (3) and then sputters the aluminum film layer. Compared with Example 4 in which step (3) is not performed, the salt spray resistance time in Example 1 is 572 hours, and the weight loss in the wear resistance test is 10%, the bonding force is as high as 28.4 MPa, and the high-temperature demagnetization rate is 0.5%. However, the salt spray resistance time in Example 4 is only 548 hours, and the bonding force is reduced to 26.5 MPa. The weight loss in the wear resistance test and the high-temperature demagnetization performance are both reduced compared with Example 1. This shows that the present invention can improve the corrosion resistance and magnetic properties of NdFeB magnetic materials under the condition of the same composite anti-corrosion coating thickness by preferably performing ion bombardment cleaning first and then sputtering the aluminum film layer.
[0111] (3) Combining Example 1 and Example 5, it can be seen that the nitriding temperature in Example 5 is too high, resulting in a significant decrease in high-temperature demagnetization performance, but the anti-corrosion performance is not significantly improved. This shows that the present invention preferably controls the nitriding temperature within a reasonable range, which can simultaneously ensure excellent anti-corrosion performance and high-temperature demagnetization performance;
[0112] (4) It can be seen from Example 1 and Example 6 that the current of arc spraying in Example 6 is relatively high, which reduces the magnetic properties of the NdFeB magnet compared with Example 1, and the binding force is reduced to 27.8 MPa. This shows that the method for preparing the NdFeB magnetic material with a composite anti-corrosion coating provided by the present invention sets the current of arc spraying within a reasonable range, which can better ensure excellent anti-corrosion performance and high-temperature demagnetization performance at the same time;
[0113] (5) In Comparative Example 1, no sandblasting was performed, resulting in the bonding strength of the composite anti-corrosion coating decreasing to 18.4 MPa. In Comparative Example 2, since no aluminum film layer was set, not only the bonding strength decreased, but also the salt spray resistance time was only 384 h, the high-temperature demagnetization rate was as high as 2%, and the high-temperature resistance performance was also significantly reduced. In Comparative Example 3, magnetron sputtering was used to sputter the aluminum alloy coating. Not only did it take 300 minutes to sputter a 68.5 μm aluminum alloy coating, but it was also difficult to reach the thickness of the aluminum alloy coating of Example 1, and the final bonding strength and salt spray resistance time were significantly reduced, indicating that the combination of arc spraying and magnetron sputtering is very critical to the comprehensive performance of the final NdFeB magnetic material. In Comparative Example 4, no nitriding or passivation treatment in step (5) was performed, and the anti-corrosion performance and wear resistance were significantly reduced.
[0114] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a NdFeB magnetic material with a composite anti-corrosion coating, characterized in that: The preparation method comprises the following steps: Performing sandblasting on the NdFeB substrate to obtain a sandblasted NdFeB substrate; An aluminum alloy coating is sprayed on the surface of the sandblasted NdFeB substrate by an arc spraying method to obtain a first substrate; sputtering an aluminum film layer on the surface of the aluminum alloy coating of the first substrate by a magnetron sputtering method to obtain a second substrate; The second substrate is subjected to plasma nitriding treatment or passivation treatment to obtain a NdFeB magnetic material with a composite anti-corrosion coating.
2. The preparation method according to claim 1, characterized in that: The blasting material of the sandblasting comprises brown corundum and / or quartz sand; And / or, the blasting material particle size of the blasting is 14 to 40 mesh; And / or, the sandblasting pressure is 0.1-0.5 MPa; And / or, the sandblasting time is 5 to 15 minutes.
3. The preparation method according to claim 1 or 2, characterized in that: In the arc spraying method, the angle between the arc spray gun and the conductive nozzle is 30 to 60°; And / or, the diameter of the aluminum alloy wire in the arc spraying method is 2 to 3 mm; And / or, in the arc spraying method, the distance between the arc spray gun and the workpiece surface is 150 to 200 mm; And / or, the working voltage in the arc spraying method is 30 to 35 V; And / or, the working current in the arc spraying method is 180-220A; And / or, the pressure of the compressed air in the arc spraying method is not less than 0.5 MPa; And / or, the flow rate of compressed air in the arc spraying method is not less than 2.0m 3 / min.
4. The preparation method according to claim 1, characterized in that: The thickness of the aluminum alloy coating is 50 to 200 μm; And / or, the aluminum content in the aluminum alloy coating is 80 to 90 at%; And / or, the material of the aluminum alloy coating includes any one of aluminum-nickel alloy, aluminum-titanium alloy, aluminum-chromium alloy or aluminum-magnesium alloy, or a combination of at least two thereof.
5. The preparation method according to claim 1, characterized in that: Between the sprayed aluminum alloy coating and the sputtered aluminum film layer, the preparation method further comprises: sequentially performing baking degassing and ion bombardment cleaning on the first substrate.
6. The preparation method according to claim 1, characterized in that: The vacuum degree in the magnetron sputtering method is 6.5×10 - 3 Pa~3.0×10 -3 Pa; And / or, the working gas pressure in the magnetron sputtering method is 0.1-1 Pa; And / or, when the magnetron sputtering method adopts a through-type magnetron sputtering coating production line, the sputtering current is 50-80A and the sputtering time is 10-20min; or, when the magnetron sputtering method adopts a single-body coating machine, the coating current is 10-30A and the coating time is 20-60min; And / or, the thickness of the aluminum film layer is 1-2 μm.
7. The preparation method according to claim 1, characterized in that: The vacuum degree of the plasma nitriding treatment is 1-10 Pa; And / or, the nitriding temperature of the plasma nitriding treatment is 200-300° C.; And / or, the nitriding time of the plasma nitriding treatment is 20 to 60 minutes; And / or, the gas used in the plasma nitriding treatment is NH3; And / or, the nitriding gas pressure of the plasma nitriding treatment is 100-600 Pa; And / or, the current density of the plasma nitriding treatment is 0.5-5 mA / cm 2 ; And / or, the voltage of the plasma nitriding treatment is 600-800V; And / or, the passivation solution of the passivation treatment comprises a passivating agent, and the passivating agent comprises any one or a combination of at least two of potassium molybdate, sodium molybdate or nitric acid; And / or, the passivation time of the passivation treatment is 4 to 15 minutes; And / or, the passivation temperature of the passivation treatment is 30-50°C.
8. The preparation method according to claim 1, characterized in that: The composition of the NdFeB matrix includes 28.5-32wt% of R element, 0.86-1.02wt% of B element, 0-4wt% of M element excluding 0, and the balance T; Wherein, R represents a rare earth element selected from Nd and at least one of the following rare earth elements: Pr, La, Ce, Dy, Tb and Ho; M is selected from any one or a combination of at least two of Cu, Ga, Zr, Ti, Nb, Al, Ag, Co or W; T includes Fe and other impurity elements, wherein Fe accounts for more than 97 wt % of the total T amount.
9. A NdFeB magnetic material with a composite anti-corrosion coating, characterized in that: The NdFeB magnetic material with a composite anti-corrosion coating is prepared by the method for preparing the NdFeB magnetic material with a composite anti-corrosion coating according to any one of claims 1 to 8.
10. Use of a NdFeB magnetic material obtained by the preparation method according to any one of claims 1 to 8 and / or a NdFeB magnetic material with a composite anti-corrosion coating according to claim 9 in automobiles, electrical appliances, new energy or medical equipment.
Citation Information
Patent Citations
Neodymium-iron-boron magnet composite coating and preparation method thereof
CN116356314A